Estructuración de un proyecto de expansión que sea aplicable a la industria de caramelos Pérez Bermeo - Cabezas Galarza, Karina Gabriela (2007)
The proposal we offer to develop this project is to address all this important market, started with the local market with a new product that has a planned organizational structure supported by a newly formed Marketing, which is able to identify and resuscitate positioning of the lost or rather not widespread in the years of work that until today has been developing Perez Candy Industry Bermeo brand.